Paecilins F–P, new dimeric chromanones isolated from the endophytic fungus Xylaria curta E10, and structural revision of paecilin A - Wei, Pan-Pan; Ai, Hong-Lian; Shi, Bao-Bao; Ye, Ke; Lv, Xiao; Pan, Xiao-Yan; Ma, Xu-Jun; Xiao, Dan; Li, Zheng-Hui; Lei, Xin-Xiang (Frontiers in Microbiology, 2022)
Eleven new dimeric chromanones, paecilins F-P (2–12), were isolated from the endophytic fungus Xylaria curta E10, along with four known analogs (1, 13–15). Their structures and absolute configurations were determined by extensive experimental spectroscopic methods, single-crystal X-ray diffraction, and ECD calculations. In addition, the structure of paecilin A, which was reported to be a symmetric C8-C8 dimeric pattern, was revised by analysis of the NMR data, and single-crystal X-ray diffraction. Compound 1 showed antifungal activity against the human pathogenic fungus Candida albicans with a minimum inhibitory concentration of 16 μg/mL, and Compounds 8 and 10 showed antibacterial activity against the gram-negative bacterium Escherichia coli with the same minimum inhibitory concentration of 16 μg/mL.